Study the effect of insecticide (chlorpyrifos) on sperm in white mice - Abdel Samie, Zainab Mokhtar (Al-Mukhtar Journal of Sciences, 2010)
The study aimed to investigate sperm effects of the orgarophosphorus insecticide Dursban in whit rats .40 male rats were orally treated with the insecticide in one does 2mg/km (20 male/dose) for 4weeks . an other 20 male were served as a control group .The tests weights were significantly decreased in the treated group compared to the control .sperm cell count ,motility variation were also increased morphological examination revealed marked effects in the treated group in the form of increased sperm abnormalities compared to the control group ,many forms of sperm abnormalities in the tail and head .